The Relationship Between Stunting and Malnutrition with Toddler Development 24-59 Months - Permata Sari, Putri; Rita Aninora, Novia; Wikarya, Rionitara (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Stunting is a health problem that is often found in developing countries, including Indonesia. Many factors can cause high rates of stunting in toddlers. This stunting problem certainly not only affects children's growth but also their development. Objective: The aim of this research is to determine the relationship between stunting and malnutrition Toddler Development Aged 24-59 Months at Alai Health Center, Padang City Method: he research design used is quantitative with a cross-sectional approach which aims to describe the relationship between stunting and malnutrition with the development of toddlers aged 24-59 months in the Alai Health Center area, Padang City in 2024. Result and Discussion: The results of the study showed that out of 46 respondents with malnutrition status and abnormal development, there were 31 children (46.9%) with questionable development, there were 6 children (23%), while those with normal malnutrition with abnormal development were 2 children (3.1%) and those with questionable development were 7 children (27%). Based on the statistical test or Fisher's Excat Test, the p value was obtained 0.001. Conclusions: Researchers' efforts as health workers should increase mothers and families' awareness of the importance of toddler growth and development and the foods that should be consumed, especially those related to providing complementary foods to breast milk for babies.